Genetic variants in FH are associated with renal histopathologic subtypes of lupus nephritis: a large cohort study from China. (October 2017) - Tan, M; Hao, J-b; Chu, H; Wang, F-m; Song, D; Zhu, L; Yu, F; Li, Y-z; Song, Y; Zhao, M-h
Objective: Genetic variants in FH (complement factor H) were reported to associate with susceptibility to systemic lupus erythematosus (SLE). This study proposed that the genetic defects of FH in the susceptibility and in the development of lupus nephritis might be different. Methods: This study enrolled 334 lupus nephritis patients, 269 SLE patients without clinical renal involvement and 350 controls. Two-step genotyping was performed. First, all the exons of the FH gene were fully sequenced in 100 lupus nephritis patients and 100 healthy controls. Second, genotyping of three common variants reported to be functional, rs1061170, rs800292 and rs6677604, was conducted in all the recruited individuals. Further, analysis of their associations with SLE/lupus nephritis susceptibility and the clinico-pathological parameters in the lupus nephritis group was performed. Results: No significant differences were observed in allele and genotype frequencies of the three single nucleotide polymorphisms between lupus patients and controls. There was a significantly higher ratio of CC/CT genotypes of rs1061170 in lupus nephritis patients with class III than in the other two classes (class III vs. class IV vs. class V: 21.0% vs. 9.7% vs. 9.4%; P  = .044). The rs6677604-GG genotype was observed to be associated with the absence of anti-ds DNA antibody ( P  = .021), and the rs800292-TT genotype was associated with a higher level of circulating C3 ( P  = 0.20) in lupus nephritis. Conclusion: In an independent cohort, this is the first genetic association analysis focusing on FH genetic variants in Chinese lupus nephritis patients. It was found that the variants in the FH gene might affect the histopathologic subtypes and some clinical features of the disease.